Clinical practice guidelines for biliary atresia in Japan: A secondary publication of the abbreviated version translated into English. (4th October 2020) - Ando, Hisami; Inomata, Yukihiro; Iwanaka, Tadashi; Kuroda, Tatsuo; Nio, Masaki; Matsui, Akira; Yoshida, Masahiro
Abstract: The purpose of this study was to prepare clinical practice guidelines for biliary atresia according to the Medical Information Network Distribution Service (MINDS) Handbook for Clinical Practice Guideline Development 2014. The guideline drafting group determined 25 clinical questions (CQs) essential for daily clinical practice. These CQs were grouped into the following four major categories: diagnosis, treatment, complications, and prognosis. A systematic literature search was performed by the systematic review team, and medical evidence was extracted from articles published until July 2014 on PubMed and the Japan Medical Abstracts Society. To reach a consensus, majority voting (>70%) of the panel of the guideline drafting group was adopted according to the Delphi technique. Recommendations for 21 CQs were appropriately provided. However, for four CQs (CQ2, stool color; CQ9, steroid administration; and CQ24 and CQ25, liver transplantation), recommendations could not be determined due to a scarcity of evidence. The first clinical practice guidelines for biliary atresia were successfully created using procedures recommended by the MINDS. It is expected that these guidelines will be used worldwide, and that the standardization of biliary atresia treatment will improve treatment outcomes. Abstract : Highlight The first clinical practice guidelines for biliary atresia in Japan were developed by the Japanese Biliary Atresia Society, consisting of 25 clinical questions in four categories: diagnosis, treatment, complications, and prognosis. Recommendations for 21 clinical questions are provided, while four clinical questions lack recommendations due to a scarcity of evidence.